2019
DOI: 10.1021/acs.jnatprod.8b00964
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin Increases Paclitaxel-Induced Cell Death and Overcomes Paclitaxel Resistance in Breast Cancer Cells through ERK-Mediated Apoptosis Induction

Abstract: ERK is a component of mitogen-activated protein kinases that controls a range of cellular processes including cell proliferation and survival. The upregulation of ERK has been associated with apoptosis inhibition in response to various stimuli including chemotherapeutic agents. Research has suggested that the upregulation of ERK signaling by the anticancer agent paclitaxel leads to acquired resistance of cells to this compound. The presented research focused on determining the role of plumbagin, a naturally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…MDA-MB-468 cells were treated with ChPL (μM) and PTX (nM) at the following fixed combinations: 0.1/0.1; 0.2/1; 0.5/5; 1/10; 2/20. The combination index (CI) was calculated as previously published (Kawiak et al, 2019). Obtained CI values lower than 1 indicate synergistic activity between compounds, whereas CI values higher or equal to 1 indicate antagonistic and additive activity, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…MDA-MB-468 cells were treated with ChPL (μM) and PTX (nM) at the following fixed combinations: 0.1/0.1; 0.2/1; 0.5/5; 1/10; 2/20. The combination index (CI) was calculated as previously published (Kawiak et al, 2019). Obtained CI values lower than 1 indicate synergistic activity between compounds, whereas CI values higher or equal to 1 indicate antagonistic and additive activity, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is closely related to tumor formation. Increased expression of ERK has been detected in a variety of human tumors, especially in GC. It has been shown that the activation of ERK signaling promotes GC growth and metastasis, so it is the most important pathway in the development of GC .…”
Section: Resultsmentioning
confidence: 99%
“…This drug also inhibits the effects of other factors on the microtubule system and, together with the stable binding of microtubule proteins, eventually induces apoptosis ( Liu et al, 2017a ). In clinical applications, paclitaxel has shown good efficacy in treating non-small cell lung cancer ( Hoang et al, 2012 ), breast cancer ( Manhas et al, 2022 ), gastric cancer ( Tu et al, 2022 ), nasopharyngeal cancer ( Xia et al, 2022 ), ovarian cancer ( Kong et al, 2023 )and cervical cancer ( Yasunaga et al, 2022 ), particularly for drug-resistant tumors ( Song et al, 2018 ; Kawiak et al, 2019 ). Although the therapeutic efficacy of paclitaxel in glioma has been confirmed, its therapeutic mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%